Entrepreneurial orientation of public enterprises in Malaysia - Harry, Entebang; Harrison, Richard T.; Ernest Cyril, de Run (Emerald Group Publishing, 2010)
The results of the investigation reveal that public enterprises seemed to concentrate on incremental aspect of the marketing of true and tried products/services. Although these companies appeared to have a strong emphasis on R&D initiatives, but most of these initiatives focused on development side of the activities. In addition, the results of the study indicate that the extent to which public enterprises respond to action initiated by competitors; become the first to introduce new product/services and/or “undo the competitor posture” appeared to be quite low. On the other hand, public enterprises tended to focus on low risk projects. Hence, they prefer to explore and exploit the unknown gradually and will act when certainty exits.